Prostate specific membrane antigen (PSMA) expression in non-small cell lung cancer. - Lars Henning Schmidt; Birthe Heitkötter; Arik B Schulze; Christoph Schliemann; Konrad Steinestel; Marcel Trautmann; Alessandro Marra; Ludger Hillejan; Michael Mohr; Georg Evers; Eva Wardelmann; Kambiz Rahbar; et al. (PLoS ONE, 2017)
PSMA (prostate-specific membrane antigen) is overexpressed in prostate cancer cells and is reported to be a promising target for antibody-based radioligand therapy in patients with metastasized prostate cancer. Since PSMA expression is not restricted to prostate cancer, the underlying study investigates PSMA expression in non-small cell lung cancer (NSCLC).Immunohistochemistry was used to identify PSMA expression in n = 275 samples of NSCLC tissue specimens. By means of CD34 co-expression, the level of PSMA expression in tumor associated neovasculature was investigated. The impact of PSMA expression on clinicopathologic parameters and prognosis was evaluated.PSMA tumor cell expression in NSCLC is as low as 6% and was predominantly found in squamous cell carcinoma (p = 0.002). Neovascular PSMA expression was found in 49% of NSCLC. High neovascular PSMA expression was associated with higher tumor grading (G3/G4) (p < 0.001). Neither for PSMA tumor cell expression, nor for PSMA neovascular cell expression prognostic effects were found for the investigated NSCLC cases.Here, we report on the expression of PSMA in NSCLC tissue samples. Against the background of a potential treatment with radiolabeled PSMA ligands, our data might serve for the future identification of patients who could benefit from this therapeutic option.